Study Pengujian SEM ( Scaning Electron Microscopy ) Pada Ebonit Dengan Kandungan Sulfur 35PHR, Komposit Bermatrik Ebonit Diperkuat Serat Bambu 20PHR Dan 40PHR Serta Spion Honda Scoopy Sebagai Pembanding - Narno, Narno; , Dr. Joko Sedyono; , Ir. Ngafwan, MT (2016)
Composite is a combination of two or more pieces of material elements which are combined into one to get a new, more useful material and its constituent elements are still distinguishable. In Indonesia where natural resources such as rubber and natural fibers are very abundant so the potential for developing a composite derived from natural materials that are environmentally friendly is wide open. One of the plants that can grow almost throughout the territory of Indonesia is bamboo, so it can be developed into new materials that are more useful and high quality. One of the way is making composite natural fiber reinforced matrix ebonite bamboo. Because the basis of this study tested SEM (Scanning Electron Microscopy) against ebonite with a sulfur content 35phr, fiber-reinforced composites with matrix ebonite bamboo 20phr and 40phr as well as on the mirror Honda Scoopy. This study was done to improve kwalias of a composite material derived from natural materials especially ebonite and bamboo fiber. The results of this study were observed from SEM images ebonite has three distinct layers, composite with matrix ebonite 20phr bamboo fiber reinforced bonds between matrix and ebonite not perfect. Ebonite with matrix fiber reinforced composites 40phr bamboo fiber bonding with very strong matrix and the surface of the rear view mirror Honda Scoopy is very tight and there is no porosity